Impact of Age and Duration of Symptoms on Surgical Outcome of Single-Level Microscopic Anterior Cervical Discectomy and Fusion in the Patients with Cervical Spondylotic Radiculopathy. (30th September 2014) - Omidi-Kashani, Farzad; Ghayem Hasankhani, Ebrahim; Ghandehari, Reza
Abstract : We aim to evaluate the impact of age and duration of symptoms on surgical outcome of the patients with cervical spondylotic radiculopathy (CSR) who had been treated by single-level microscopic anterior cervical discectomy and fusion (ACDF). We retrospectively evaluated 68 patients (48 female and 20 male) with a mean age of41.2 ± 4.3 (ranged from 24 to 72 years old) in our Orthopedic Department, Imam Reza Hospital. They were followed up for31.25 ± 4.1 months (ranged from 25 to 65 months). Pain and disability were assessed by Visual Analogue Scale (VAS) and Neck Disability Index (NDI) questionnaires in preoperative and last follow-up visits. Functional outcome was eventually evaluated by Odom's criteria. Surgery could significantly improve pain and disability from preoperative6.2 ± 1.4 and22.2 ± 6.2 to3.5 ± 2.0 and8.7 ± 5.2 (1–21) at the last follow-up visit, respectively. Satisfactory outcomes were observed in 89.7%. Symptom duration of more and less than six months had no effect on surgical outcome, but the results showed a statistically significant difference in NDI improvement in favor of the patients aged more than 45 years (P = 0.032 ), although pain improvement was similar in the two groups.